The Correlation between Physical Environmental Factors and Fatigue of The Workers at Ship Repair Workshop - Aulia Nur Pratiwi (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: Fatigue is a body protection mechanism that prevents further detriments and can be recovered after having a sufficient amount of rest. The fatigue undergone by workers is one of the causes of occupational accidents. Fatigue can be triggered by several factors, such as physical environments, for instance, temperature and noise. This research aims to analyze the relationships between the temperature as well as the noise and the work fatigue of the workers at the area of ship repair workshop at PT. X Surabaya. Methods: This research is descriptive observational research that employs the cross-sectional design. The sample of this research, the total population, consists of 32 people. The data is obtained through the temperature measurement by utilizing hygro-thermometer, the noise intensity measurement by utilizing the sound level meter, and the levels of work fatigue measurement by utilizing reaction timer. Those measurements are completed in two different locations, namely the office and the workshop. The strength of the relationships among variables is scrutinized by applying the spearman correlation test by studying the correlation coefficient value. Results: Show that 14 people (43.8%) do not suffer from any fatigue, 15 people (46.9%) suffer from mild fatigue, 2 people (6.2%) suffer from moderate fatigue, and 1 person (3.1%) suffers from severe fatigue. The fatigue is mostly undergone by the workers exposed to the overheat temperature, that is as many as 18 people (56.2%) and by those who are exposed to noise, which are 15 people (46.9%). Conclusion: There is a moderate relationship between the temperature and the fatigue (p=0.519). Meanwhile, the noise (p=0.688) has a strong relationshipship with the fatigue undergone by the workers at the area of ship repair workshop at PT. X Surabaya. Keywords: noise, ship reparation, temperature, work fatigue